Long-term adverse events of three COVID-19 vaccines as reported by vaccinated physicians and dentists, a study from Jordan and Saudi Arabia. Issue 1 (31st December 2022) - Dar-Odeh, Najla; Abu-Hammad, Osama; Qasem, Farah; Jambi, Safa; Alhodhodi, Aishah; Othman, Ahmad; Abu-Hammad, Abdalla; Al-Shorman, Hisham; Ryalat, Sukaina; Abu-Hammad, Shaden
ABSTRACT: Assessment of safety of COVID-19 vaccines is an ongoing process. This study aims to explore long-term adverse events reported by physicians and dentists who received at least two COVID-19 vaccine doses. A group of physicians and dentists were invited to complete a validated questionnaire that was composed of items on: socio-demographics, medical history, administered vaccines, and long-term adverse events (LTAE). Data of a total of 498 practitioners were included. Age ranged from 22 to 71 years (mean age = 35.75 ± 11.74) with a female majority (N = 348, 69.9%). The most frequently administered vaccines were Pfizer-BioNtech, Sinopharm and AstraZeneca vaccines. A total of 80 (16.0%) participants reported LTAEs which were mainly fatigue, menstrual disturbances, myalgia, arthralgia, dizziness, and headache (N = 32, 15, 8, 6, 4, and 4, respectively). There was no statistically significant association between LTAEs and: age, gender, or medical history ( P > .05). The collective symptoms of fatigue, myalgia, arthralgia, dizziness, and headache were significantly associated with Sinopharm vaccine ( P = .04). This was further confirmed by general linear multivariate model analysis. Less than 20% of COVID-19 vaccine recipients may complain of LTAEs that are mostly fatigue-related. It seems that factors such as age, gender, and medical status play a negligible role in development of these AEs. On the other hand, Sinopharm vaccine showed the highest significant association with these AEs followed by AstraZeneca vaccine.